Penerapan Model Pembelajaran Demi Terwujudnya Peningkatan Kesadaran Peserta Didik Mengenai Proklamasi Kemerdekaan Indonesia - Aulia Nisa Asyani; Siti Fatimah; Muh Husen Arifin; Tuti Istiani (Institut Pendidikan Indonesia, 2021)
The background of this research is related to the development of human resources through social sciences which must be introduced to students from an early age. Of course, in the introduction of social studies, teachers must use learning models so that teaching and learning activities can be achieved in accordance with learning objectives. The formulation of the problem in this research article is how does a teacher deliver learning related to social studies?. In addition, what learning models can teachers use in teaching social studies? The purpose of this study is so that readers can understand various learning models that can be used in increasing students' understanding of the Proclamation of Indonesian Independence. This study uses qualitative research methods that use data types in the form of results from journal literature, books, and other scientific works as a reference for writing research. The results of this study indicate that there are several learning models that can be used by educators in teaching and learning activities about the Proclamation of Indonesian Independence. Keywords: Learning Model, Social Studies, Human Resources, Proclamation of Indonesian Independence